Gamified Learning in Tennis: The Impact of Manipulative Motor Skill Levels on Forehand Groundstroke Performance - Rusdiyanto, Rajip Mustafillah; Wiguno, Lokananta Teguh Hari; Kurniawan, Ari Wibowo (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2025)
This study aims to analyze the effect of a gamification approach on the improvement of basic forehand groundstroke skills in students with high and low levels of manipulative ability. The research method used a quantitative approach with a two-way mixed experimental design (2WMD), involving one between-subject factor, namely manipulative ability (high and low), and one within-subject factor, namely measurement time (pre-test and posttest). The study sample was students of the Physical Education, Health, and Recreation Study Program at the State University of Malang who had taken tennis courses. Data were collected through a basic forehand skills test and an observation rubric based on the TGMD-3. The analysis results showed a significant increase in forehand skill scores between the pre-test and posttest (F(1,58) = 911.969; p < 0.05; η² = 0.940). There was also a significant difference between the high- and low-manipulative-ability groups (F(1,58) = 151.932; p < 0.05; η² = 0.724). In addition, a significant interaction was found between measurement time and manipulative ability (F(1,58) = 26.940; p < 0.05; η² = 0.317). These findings confirm that the gamification approach is effective in increasing students’ motivation and motor skills through structured practice, direct feedback, and active involvement in sports learning.